Shoreline Detection Using TerraSAR-X Quad Polarization Mode - Gurreonero Robinson, Diego A.; Bijker, Wietske; Tolpekin, Valentyn A. (The International Hydrographic Review, 2013)
In the Netherlands, the coastal zone is a dynamic area because of the geographic position. Economic activities and effects of global warming demand a frequent, accurate and detailed update of the coastline information. For this study, TerraSAR-X quad polari-zation was obtained at 6.6 m azimuth resolution during the Dual Receive Antenna (DRA) campaign. The coastline is detected by decomposing the polarimetric SAR components in three different scattering mechanisms: volume scatter, double bounce scatter, and surface scatter. This composite scattering model allows to classify the image based on these dif-ferent scattering mechanisms. After the decomposition, region growing segmentation is applied to group neighboring pixels with similar values to identify the coastline as the boundary between land and sea. Scheveningen beach has been chosen as case study. The primary methodology is the Freeman and Durden decomposition followed by two clas-sifications (1) Wishart supervised with Maximum Likelihood and without supervised classi-fication and region growing segmentation or (2) with segmentation applied directly to the decomposition results. The output segmentation vector is validated by comparing with nautical charts. After the decomposition and classification of the scatter mechanism, statis-tics showed good signature separability. The region growing segmentation gives good out-puts according to the difference in group pixels related to the land and those related to the sea.